2021
DOI: 10.1002/adfm.202104787
|View full text |Cite
|
Sign up to set email alerts
|

Fast Photothermoelectric Response in CVD‐Grown PdSe2 Photodetectors with In‐Plane Anisotropy

Abstract: PdSe2, a star photosensitive functional material, has been successfully used in photodetectors based on sensing mechanisms of photogating, photoconductive, and photovoltaic effects. Here, a photothermoelectric (PTE) effect is observed in photodetectors based on PdSe2 flakes grown by chemical vapor deposition. The unique photoresponse arises from an electron temperature gradient instead of electron–hole separation. Direct evidence of the PTE effect is confirmed by a nonlocal photoresponse under zero bias. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…The Pd 3d 3/2 and 3d 5/2 peaks located at 341.7 and 336.5 eV and the Se 3d 3/2 and 3d 5/2 peaks located at 55.1 and 54.3 eV for as-exfoliated PdSe 2 crystals are consistent with the characteristic binding energies of PdSe 2 crystals. [20,32,39] An unknown peak (*) is found at ≈51 eV. Since the bulk PdSe 2 was grown by the self-flux method and the remaining Se and other residues were not removed from PdSe 2 crystals before the transfer, this peak may be due to the residual element.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pd 3d 3/2 and 3d 5/2 peaks located at 341.7 and 336.5 eV and the Se 3d 3/2 and 3d 5/2 peaks located at 55.1 and 54.3 eV for as-exfoliated PdSe 2 crystals are consistent with the characteristic binding energies of PdSe 2 crystals. [20,32,39] An unknown peak (*) is found at ≈51 eV. Since the bulk PdSe 2 was grown by the self-flux method and the remaining Se and other residues were not removed from PdSe 2 crystals before the transfer, this peak may be due to the residual element.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with that of previous studies. [20,32,49,50] The anisotropic intensity of the g 1 A peak in the ( ) z xx z configuration is shown with the crystal axes in the crystal image in Figure 1e. This anisotropic behavior makes it possible to determine the crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the inherent low lattice thermal conductivity, lower-symmetry materials have been widely used in thermoelectric applications. Considering the high carrier mobility and large Seebeck coefficient (>200 μV·K –1 ) of PdSe 2 , , the efficient detection for THz waves could be realized by the photothermoelectric (PTE) effect. Previous reports have demonstrated that it can respond from the visible to the mid-infrared (4.05 μm) and expand to the long-wavelength infrared (10.6 μm) via heterogeneous integration with other 2D materials. , Notably, these PDs involve solely the usage of bandgap-matching with incident photons limiting the application of broad-spectrum and self-powered devices. For instance, the photoconductive mechanism of single-material PDs driven by external voltage introduce a bandgap-related response with a non-negligible noise signal and energy consumption …”
mentioning
confidence: 99%
“…18–21 Recently, some pentagonal materials such as Penta-PdSe 2 , Penta-PdPSe, and Penta-NiN 2 have been synthesized experimentally, ensuring the experimental synthesis possibility and research value of these pentagonal materials. 22–24…”
Section: Introductionmentioning
confidence: 99%